Female Headed Households in Early Modern Kyoto, Japan - Nagata, Mary Louise (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2017)
Abstract: This study examines female-headed households in the late Tokugawa era in Kyoto, Japan, 1843-1868. The study uses a data set of 37,000 person-year observations from individual faith surveys (also known as population registers) compiled by 30 neighborhoods in Kyoto, supplemented by qualitative documents to compare those households listing a female head with those listing a male head or a child aged 1-10 as the head of household. The number of households listing women or children as head, despite the presence of adult males, already suggests that headship was not about patriarchal authority. This study of female-headed households therefore examines the significance of listing women as head of household and what female headed households reveal about gender, headship and family in mid-nineteenth century Kyoto during the final years of the Tokugawa regime. Key words: Female headed households, headship, marriage, inheritance, children, property Resumen: El presente trabajo examina los hogares con jefatura femenina en la era Tokugawa tardía (1843-1868) en Kioto, Japón. Se usó un conjunto de datos de 37.000 observaciones año-persona de encuestas individuales (también llamadas registros de población) compiladas por 30 barrios en Kioto y complementadas por documentos cualitativos para comparar los hogares con jefatura femenina con aquellos que tenían a un niño entre uno y diez años como jefe de hogar. La cantidad de hogares que registraron mujeres o niños cabeza de hogar, a pesar de la presencia de hombres adultos, sugiere que la jefatura no estaba relacionada con la autoridad patriarcal. Por lo tanto, el estudio de hogares con jefatura femenina examina el significado de los registros de mujeres como cabeza de hogar y lo que este tipo de hogares refleja sobre el género, la jefatura y la familia en el Kioto de mediados del siglo XIX, durante los últimos años del régimen Tokugawa. Palabras clave: Hogares con jefatura femenina, jefatura, matrimonio, herencia, hijos, propiedades doi: https://doi.org/10.20318/revhisto.2017.3705